A simple and effective strategy based on sodium gallate-exfoliated graphene for the simultaneous voltammetric determination of guaiacol and vanillin. Issue 32 (5th August 2019) - Li, Chenchen; Fu, Ju; Tan, Xiaohong; Song, Xinjian; Li, Qunfang
Abstract : A highly sensitive graphene-based sensor for the simultaneous determination of guaiacol and vanillin was constructed simply and effectively. Abstract : High concentration graphene nanosheets were easily prepared through simple liquid-phase exfoliation of graphite powder in N, N -dimethylformamide with the assistance of sodium gallate (SG). The concentration of the obtained graphene dispersion reached 2.0 mg mL −1 only after three hours of ultrasonic treatment. Sodium gallate-exfoliated graphene nanosheets (SG-GNs) showed remarkable signal enhancement effects toward the oxidation of guaiacol and vanillin. In this regard, the composite was used to develop a sensitive and rapid electrochemical method for simultaneous determination of guaiacol and vanillin. The method had a wide linear range of 0.02–12 μM for guaiacol and 0.02–11 μM for vanillin, and low limits of detection of 5 and 4.5 nM, respectively. The developed sensor also exhibited superior accuracy for analysis of real food samples. Therefore, the proposed sodium gallate-assisted exfoliation strategy shows great potential for scalable preparation of graphene suspensions and electrochemical sensing.